Insertion of orthodontic temporary anchorage devices with free gingival grafting for phenotype modification of the peri-implant mucosa - Oscar Maldonado Molina (Elsevier, 2023)
Background: Mini Implants are widely used in contemporary orthodontics, they provide skeletal anchorage even in non-compliant patients, facilitate orthodontic tooth movement, are easy to place and are relatively inexpensive. Their failure is multifactorial, and the quality of the soft tissue can present a risk limitation for the insertion of TADS. Orthodontic Mini Implants inserted in keratinized gingiva present fewer tissue-related complications and higher survival rate, than those inserted in non-keratinized mucosa. The purpose of this report is to present and describe this novel technique to modify and enhance the peri-implant mucosa of Orthodontic Mini Implants inserted in nonkeratinized gingiva. Methods: A free gingival graft was harvested from the palate in combination with a buccal recipient site preparation in the alveolar mucosa and a TAD insertion procedure. Results: After twenty-one days of healing, graft integration was observed. One hundred and eighty days after insertion and twelve weeks of loading, none to mild signs of clinical inflammation were documented, and the patient reported no pain or discomfort. Conclusion: Within the limitations of this report, free gingival grafting for phenotype modification of the peri-implant mucosa, can benefit patients who need insertion of orthodontic mini-implants in non-keratinized mucosa for orthodontic tooth movement.